Joint Next-Hop/Relay Selection for Distributive Multihop Cooperative Networks. (9th December 2015) - Alkhayyat, Ahmed
Abstract : Cooperative networks that use adjacent nodes to relay hearing data are employed as an effective technique to deal with channel fading, thereby enhancing the network performances. Next-hop and relay nodes selection schemes determine the optimal next-hop node toward the destination and relay node between the source and the optimal next-hop and/or destination. Offering joint next-hop and relay node selection in distributive multihop cooperative networks will enable the source to select the optimal next-hop node and relay node that can improve the system performance. In this paper, we propose a joint next-hop node and relay node selection (JNRS) protocol for wireless distributive multihop cooperative networks. The goal of JNRS is to reduce the spectral efficiency loss and outage probability. Analysis results show that JNRS can enhance the cooperative networks performance under general conditions compared to cooperative networks without the JNRS protocol.